Kesan intervensi awal berasaskan keibubapaan dan teknologi bantuan terhadap kemahiran literasi awal Bahasa Inggeris kanak-kanak sindrom down / Ng Poi Ni - Ng , Poi Ni (2016)
Past studies in literacy learning have shown that children with Down syndrome are capable of reading in English, but with varied levels of achievements. These different levels of achievement may be due to the applied teaching approach, the influence of the children’s environment and the role of parents in literacy practices at home. Therefore, this single-subject study sets out to examine the effectiveness of a parental and assistive technology based early literacy intervention on the reading proficiency of children with Down syndrome. An evaluation of effectiveness of this intervention was carried out through multiple-baseline of probes sessions, replicated across participants in a home setting. In addition, for triangulation purpose and social validity, this study also investigated the involvement of children with Down syndrome during the intervention process, as well as the experience and views of their parents on the use of assistive technology and involvement of parents in the intervention. The conceptual framework of this study emphasized on the role of three key elements: namely, early literacy intervention programme, the role of parents and the role of assistive technology. All the three elements were interconnected and essential in order to boost the achievement level of early literacy skills among children with Down syndrome. Therefore, four children aged 4 to 5 years with Down syndrome and their parents were purposely selected as subjects for the study. Fieldwork, which was carried out for the duration of twelve months, were divided into four main phases: pre-study phase, baseline phase, intervention phase and maintenance phase. Quantitative data collection was via pre-test, post-test and delayed post-test. Correspondingly, qualitative data was collected through various methods such as observations, interviews and questionnaires on parent’s social validity. The findings showed that the four children with Down syndrome had successfully mastered most (80 %) of the early literacy skills that had been taught to them. These skills include; letter name and letter sound naming, beginning sound awareness and phonological word reading. On the contrary, the whole-word reading skill was only mastered well by one of the subjects. In fact, the study also found that children with Down syndrome showed positive involvement during the intervention process. On top of that, the Down syndrome children and their parents were found to have experienced changes in the socio-emotional meaning. This finding has proven early literacy intervention planning based on parents and technology may help motivate learning among children with Down syndrome. Moreover, the parents’ interview data and social validity questionnaires indicated positive perceptions of this early literacy intervention. The insights of the study will contribute to the existing literature in the area of early learning literacy skills for children with Down syndrome: in which phonological awareness approach is more meaningful for them. Hence, the findings will also contribute to the development of early literacy intervention programmes: as a successful intervention depends on the provided intervention programme plan, the usage of assistive technology and most importantly the parents’ roles that function as a catalyst as proven by its effectiveness.